Crisis Management on the Basis of the Marketing Approach for Development of Innovative Potential of the Organization - Zhabin, Alexander P.; Suraeva, Maria O.; Evdokimov, Anatoly N.; Polynova, Lyudmila V.; Akopyan, Diana A.; Chertykovtsev, Valery K.; Grigoryants, Igor A. (International Review of Management and Marketing, 2016)
This article describes the problem of efficiency of functioning of the organization in modern conditions of dynamic external environment. Modern external environment characterized by financial instability, lower incomes, economic constraints in relation to Russia, as well as constantly changing consumer preferences caused by other factors. In such circumstances, it becomes important domestic market. Close attention should be paid to the innovative capacity of organizations in the predominant direction of innovative development of the Russian economy as a whole to deal with these unstable conditions. Describes the factors the marketing environment the organization's operations and their impact on its activities. The authors propose a methodology of determining the stability of the organization based on the analysis of environmental factors. This method may be supplemented in the study and to identify other factors of importance in the organization. The authors also proposed the algorithm of marketing management organization based on the assessment of the stability of the organization at this point in time and compare it with the desired level of stability. If defined an unsustainable situation, it is necessary to take measures of administrative influence, which is based in particular on innovation management in organization in order to achieve the desired level of stability. Keywords: sustainability, innovation, management, marketing, innovative economy JEL Classifications: M19, M29, M52, M59